Synthesis Of Biofoam Based On Glucomannan Porang And Polyvinyl Alcohol (PVA) With The Addition of Seaweed Dregs - Rusdianto, Andrew Setiawan; Amilia, Winda; Nurjannah, Rifdah Nada (Food, Agriculture and Natural Resources - NETWORKS, 2024)
Biofoam (Biodegradable foam) is an alternative packaging to Styrofoam made from natural raw materials that can be biodegraded in the soil. Biofoam is generally made from 3 constituent materials in the form of main ingredients in the form of starch or other similar materials, plasticizers such as PVA and also fillers in the form of fibers containing cellulose. The purpose of this study was to determine the effect of the combination of porang glucomannan, PVA and seaweed pulp on biofoam and to determine the best formulation and characteristics of the biofoam samples made.. The technique of making biofoam was done using baking technique with 9 different treatments. Each treatment was repeated 3x and observations were made on biofoam structure, mechanical properties testing (tensile strength, elongation and young modulus), water absorption test, and biodegradation test. The results showed that Polyvinyl Alcohol plays a role in the formation of a hollow biofoam structure. The thickness parameter value for each treatment was 0.628-1.939 mm. The tensile strength value of each treatment has a value ranging from 15.989-35.265 N/mm². The elongation value for each treatment ranged from 25.719-76.427%. The young modulus value for each treatment ranged from 0.343-0.896 N/mm². The water absorption value of each treatment obtained values ranging from 35.81-77.12%. And the value of testing biodegradation parameters obtained values ranging from 8.68-32.18%. So that the best treatment obtained using the multiple attribute method is the A3B1 treatment (PVA 15% and the ratio of seaweed pulp concentration to glucomannan 1: 2).